DEVELOPMENT OF MATHEMATICS STUDENT WORKSHEET BASED ON REALISTIC AND ISLAMIC NUANCES IN THE SOCIAL ARITMETICS SUBJECT OF CLASS VII SMP / MTs - Dewi Astrianie; Uus Kusdinar (Universitas Ahmad Dahlan, 2018)
This research is based on the unavailability of student worksheets as one of the learning resources. Saturation and lack of skilled students doing exercise questions. SW that used realistic concept and Islamic nuance is one alternative to reduce the problem. This study aims to develop and test the feasibility of Student Worksheet (SW) based on realistic and nuances Islamic in the social arithmetic subject for class VII Junior High School (SMP/MTs). This research method used Research and Development (R & D) covering the stage of preparation, implementation, testing, and revision. Material experts and media experts do SW validation. The subjects of the study were students of grade VII SMP / MTs. The instrument used is a questionnaire instrument—the analysis technique used qualitative descriptive analysis. The result of the research and development of SW shows that the material expert's assessment obtained a 75,5 score with a very good criterion, from media expert 78,3 with good criterion. The result of student response to SW is good, with a scoring average of 60,19. Based on the above, it can be concluded that SW is based on realistic and nuances Islamic in the social arithmetic subject for class VII SMP / MTs, both used as teaching materials in the learning process.